(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2022)
This text contains the report and analysis of the process of theatrical creation, belonging to the last stage of their education at an important public drama school of the State of Rio de Janeiro, developed with perspectives of autonomy and aiming at decolonial teaching, which occurred in the pandemic period, with the remote experience as an alternative for the moment.